2017
DOI: 10.4236/acs.2017.74043
|View full text |Cite
|
Sign up to set email alerts
|

Trend Analysis of Aerosol Optical Depth and &#197ngstr&#246m Exponent Anomaly over East Africa

Abstract: Trend analysis of atmospheric aerosols enhances confidence in the evaluation of both direct and indirect effects of aerosols on regional climate change. To comprehensively achieve this over East Africa, it's important to understand aerosols temporal characteristics over well selected sites namely Nairobi (1˚S, 36˚E), Mbita (0˚S, 34˚E), Mau Forest (0.0˚S -0.6˚S; 35.1˚E -35.7˚E), Malindi (2˚S, 40˚E), Mount Kilimanjaro (3˚S, 37˚E) and Kampala (0˚N, 32.1˚E). In this context, trend analysis (annual (in Aerosol Opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…On the other hand, the enhanced aerosol loading during the local dry seasons could be attributed to increased anthropogenic activities (land preparations, biomass burning and forest fires) which release significant amount of smoke particles into the EA's atmosphere (Ngaina and Muthama, ; Makokha et al ., ). The stronger near‐surface winds during JJA over the arid and semi‐arid areas of north and eastern parts of Kenya (Figure (d)) could accelerate the formation of dust aerosols.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…On the other hand, the enhanced aerosol loading during the local dry seasons could be attributed to increased anthropogenic activities (land preparations, biomass burning and forest fires) which release significant amount of smoke particles into the EA's atmosphere (Ngaina and Muthama, ; Makokha et al ., ). The stronger near‐surface winds during JJA over the arid and semi‐arid areas of north and eastern parts of Kenya (Figure (d)) could accelerate the formation of dust aerosols.…”
Section: Resultsmentioning
confidence: 97%
“…As aforementioned, the monthly variation in AOD over EA is closely associated with variations in emission sources, anthropogenic activities and seasonal cycles of precipitation. A combination of biomass burning (during December – February and June – July) and dust aerosols (locally derived and due to long‐range transport) could enhance the aerosol load during these months (Makokha et al , ). The low AOD during March–May and September–November is attributed to large wet deposition (Figure (a)) and reduced anthropogenic activities (de Graaf et al , ; Boiyo et al , ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Details and the map illustrating the study region and specifics on each site of study are as shown in [9]. .…”
Section: Description Of Study Areamentioning
confidence: 99%
“…Details and the map illustrating the study region and specifics over each site of study are as shown in [15].…”
Section: Description Of Study Area and Spectral Data Manipulationmentioning
confidence: 99%